Edukasi Kesehatan Tentang Tuberkulosis Pada Kader Surabaya Hebat Puskesmas Putat Jaya Surabaya - Sajuni Sajuni; Risma Ikawaty; Anita Purnamayanti (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
ABSTRACT Great Surabaya Cadres play a role in breaking the chain of Tuberculosis transmission. Putat Jaya Health Center has as many as 1500 Great Surabaya Cadres, and only half of the cadres have received knowledge about Tuberculosis, so that dedication was carried out to Great Surabaya Cadres at the Putat Jaya Community Health Center. The service was carried out for approximately 3 hours on March 23 2024 with a total of 48 Great Surabaya Cadres participating. The method of this service is education, providing explanations about Tuberculosis accompanied by discussions. There was a significant increase in knowledge before and after education. Keywords: Tuberculosis, education, Great Surabaya Cadres, Putat Jaya.